Predicting the collision damage of steel ring-stiffened cylinders and their residual strength under hydrostatic pressure. (1st December 2018) - Do, Quang Thang; Muttaqie, Teguh; Park, Sang-Hyun; Shin, Hyun Kyoung; Cho, Sang-Rai
Abstract: This study focusses on deriving a formulation to predict the permanent damage of steel ring-stiffened cylinders subjected to dynamic lateral mass impact and their ultimate strength in both intact and damaged conditions under hydrostatic pressure. The damage scenario considered in this study can represent the collision accidents of offshore ring-stiffened cylinder structures with supply vessels or floating objects. To validate the numerical modelling and analytical techniques, six small-scale ring-stiffened cylinder models were fabricated. Drop tests with a knife-edge indenter were performed to generate the damage on four cylinder models. Then, all the models were subjected to hydrostatic pressure tests for assessing their ultimate strength in damaged and intact conditions. Next, rigorous parametric studies on the actual design of full-scale ring-stiffened cylinder examples were performed by changing the design variables. Simple design equations were derived for predicting the extent of local denting damage and the residual strength of the damaged ring-stiffened cylinders. The accuracy of the derived formulation has been established by comparison with the results of tests and finite element analyses, showing a good agreement for all the loading cases. This formulation can be useful for the purposes of design of ring-stiffened cylinders under the risk conditions of marine structures. Highlights: Residual strength formulations of damaged ring-stiffened cylinders have been derived and proposed. A simple design equation to predict the extent of the maximum permanent dent depth of ring-stiffened cylinders under dynamic mass impact were also proposed. Nonlinear numerical methods for ring-stiffened cylinders are provided with reasonable accuracy and reliability.